HISTORIOGRAPHICAL BASIS OF THE FORMATION OF THE EUROPEAN SCHOOL OF WEAPONS (Південний архів (історичні науки), 2024)
Arms science is a separate historical discipline that was formed in the XIX–XX centuries. The European school of study was born through the interest of a certain number of like-minded people and is quite unique compared to the Asian school. The school was founded in the 19th century by former soldiers. The purpose of the research is an attempt to analyze the path of development of the historiographical foundations of the formation of the European school of weapon science and line them up in chronological order; to analyze the role of Ukraine in this process and its impact on Ukrainian science. Methodology: in the formation of the methodology of this study, a number of different elements of modern methodological systems, as well as general and special scientific methods, were used. The combined nature of the methodology of this research made it possible to draw a certain number of conclusions on the problem of studying the historiographical foundations in the formation of the European school of historical weaponry. Results: The proposed article examines the works of outstanding historians of the 19th-20th centuries. which influenced the development of historical weapon science. An analysis of historiographical sources was made, thanks to which a chronological line of the development of historical weapons science was drawn, the principles of the formation of the discipline were shown, and specific individuals and the goals and achievements of their research were considered. The article examines the role of the association of the study of historical weapons and costume in the development of the discipline of historical weaponry and its influence on this process. The article reports on Ukraine's contribution to the formation of a separate historical discipline of weapon science, namely the publication of Tiktor as a continuation of the European school of studying weapons of the past. The article reveals the influence of Begheim, an outstanding Austrian scientist, on weapon science. In the study, a comparative analysis of publications was made, the issues and current relevance were considered. Conclusions: this study fully illuminates the main factors of the formation and development of historical weapons science - a discipline that was born thanks to a number of former military officers who plunged into science. The development of historiography was determined by the interest of the scientific community of Western and Northern Europe. Ukrainian science, which was not yet under the influence of Soviet censorship, at the beginning of the 20th century published a significant study, continuing the European traditions of the historiographical development of weapons science and military history in general. The importance of the formation of historical weapon science is undeniable for understanding the issues of concepts and classification of weapons from ancient times to the present.
Keywords: Boheim, Petersen, Burton, Krechmar, Thirtbach, munitions, encyclopedia of weapons, bladed weapons, military equipment, classification of weapons, military-historical research.